Compostos de organoselênio: síntese de sais de selenônio metilado a partir de fontes renováveis de metila e selenóxidos como catalisadores em reações do tipo appel - Philipe Raphael Oliveira Campos (2024)
Following the growing concern about the correlation between the environment and the consequences of anthropogenic actions, it is expanding in the scientific community the necessity to develop new procedures in science or improve existing ones in order to reduce the generation of waste, use less toxic reagents and reduce the energy consumption. Therefore, this work is divided into two chapters, which both seek, in different ways, to develop new methodologies that are less harmful, safer and more efficient. In Chapter I, methylation reactions are discussed, which are of great interest to the areas of organic chemistry, pharmacy and medicine, as they are part of the construction of molecules through the insertion of methyl groups in strategic positions. This insertion may lead to an increase or decrease in lipophilicity, conformational changes and accentuate drug activity. It is important to highlight that commonly used methylating reagents are quite toxic, have a high cost and require care when handling them. Therefore, it is necessary to create new methylating agents that will minimize these harms in order to obtain new synthetic routes that occur in safer, more economical and versatile ways. As a result, methylated selenium salts were developed from renewable reagents such as methanol and dimethylcarbonate that were activated with sulfuric or methanesulfonic acid. Chapter II addresses the Appel reactions and their importance in developing halogenated reagents from alcohols using phosphorus compounds such as triphenylphosphine and phosphorus oxides as catalysts. Halogenated compounds can be of great interest, because it can be used as good electrophiles in nucleophilic substitution reactions, for example. On the other hand, alcohols are reagents, in general, quite stable and easy to acquire. However, the hydroxyl present in alcohols is not a good leaving group, which makes it difficult to carry out a nucleophilic substitution in compounds of this class. Therefore, it is necessary to use catalysts and/or activators in order to facilitate the exit of the hydroxyl group. With this, the activity of selenoxides as catalysts for the conversion of alcohols into chlorides, generating waste such as water, was studied. Selenoxides exhibit similar behavior to phosphine oxides due to their electrophilicity at the selenium atom and the ability to break the Se-O bond easily. Promising results were obtained, but are still under construction to better optimize the reactions.